2020
DOI: 10.1080/17436753.2020.1780552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of femtosecond laser and silica coating on the bond strength of zirconia ceramic

Abstract: Reasonable zirconia surface pretreatment results in excellent bond strength. This study compared the effects of different surface treatments on the shear bond strength of zirconia. A total of 48 zirconia discs were divided into six separate groups (n = 8) including a Control (CL), Alumina particle blasting (AP), Silica coating (SC), Alumina particle blasting and silica coating (AS), Femtosecond laser (FL) and Femtosecond laser and silica coating (FS) group. Resin block was bound with zirconia using resin cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[11] Previous studies have shown that femtosecond laser can create precisely controllable micro-scale topography on zirconia surfaces, making it a suitable noncontact method for enhancing the surface roughness of zirconia ceramics. [12][13][14] In addition to microscopic roughness, the chemical composition of the implant surface is another important factor determining osseointegration. Calcium phosphate (CP) is the primary component of bone mineral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Previous studies have shown that femtosecond laser can create precisely controllable micro-scale topography on zirconia surfaces, making it a suitable noncontact method for enhancing the surface roughness of zirconia ceramics. [12][13][14] In addition to microscopic roughness, the chemical composition of the implant surface is another important factor determining osseointegration. Calcium phosphate (CP) is the primary component of bone mineral.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Previous studies have shown that femtosecond laser can create precisely controllable micro‐scale topography on zirconia surfaces, making it a suitable noncontact method for enhancing the surface roughness of zirconia ceramics. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of a robust and long-lasting bond between resin cement and ZrO 2 is widely recognized as an essential requirement for clinical success [12]. Consequently, the objectives of this study were: (a) to compare and contrast various surface conditioning methods, in particular TBC and femtosecond laser irradiation on enclosed mold-shear bond strength (EM-SBS) between resin composite and ZrO 2 substrate, and (b) to analyze the types of failures observed during debonding.…”
Section: Introductionmentioning
confidence: 99%